ENHANCING STUDENT SATISFACTION: THE ROLE OF ACADEMIC ADMINISTRATION SERVICES IN THE FACULTY OF USHULUDDIN AND RELIGIOUS STUDIES AT UIN RADEN INTAN LAMPUNG - Qonita, Neila; Fauzan, Ahmad; Koderi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the critical role of academic administration services in enhancing student satisfaction within the Faculty of Ushuluddin and Religious Studies at UIN Raden Intan Lampung. Through a qualitative approach, the study examines various administrative practices, including student support systems, communication channels, and feedback mechanisms. By analyzing student perceptions and experiences, the research identifies key factors that contribute to their overall satisfaction and academic success. We delve into the pivotal role that efficient academic administration plays in elevating student satisfaction. By examining the intricate relationship between high-quality administrative services and positive educational outcomes, our research aims to identify specific indicators of excellent service, such as reliability, responsiveness, and empathy that significantly contribute to an enriching learning experience. Through a qualitative methods involving surveys, interviews, and focus groups among faculty members and students, we uncover compelling evidence demonstrating how robust administrative support directly impacts student engagement and overall contentment. Our analysis reveals critical areas requiring attention, such as communication gaps and delayed responses, which if addressed effectively could transform the academic landscape. Ultimately, our recommendations emphasize the necessity of ongoing training initiatives for administrative personnel coupled with strategic improvements aimed at bolstering trust and fostering a more conducive scholarly atmosphere. This investigation underscores the profound significance of meticulous academic governance in shaping superior educational environments tailored specifically towards meeting diverse student needs.